Etthical Hackers Hacking The Smart City Grid System - Mudide Ramprasad, Kasanigottu Srinivas, Talari Gangadhar (International Journal of Advanced Science and Technology, 2020)
In 21st century technology increased day to day so that people also wanted more comfortable life, these type of culture is expanded to rural area that means rural people also like urban touched living style so that urban area is expanded otherwise rural people came to travel urban area but urban area already established and fixed many more years ago, that area cant expanded so new area can plan and design future purpose. In that plan smart city are developed and implemented, smart city more comfort can use smart grid system, in this smart grid system all the facility like electricity, water, internet, etc came to one control unit and different smart city are connected in this grid that means one or more smart city are working in this smart grid.  In this paper we discussed how much it is secured and how much working up to the satisfactory mark, if smart city grid system hacking then what happened in the smart city and how to overcome this situations and how much possibility are there ethical hackers hacking the smart city grid system. Now a day’s smart grid system very helpful for smart city, this grid is interconnect to the other smart city so that smart city information easily interchanged to each other smart city’s.